Perceiving own and others behaviour:an exploration in social perception - Narain Sinha, Ran Bijay; Hassan, Arif (UNIMAS, 2015)

(untitled)
The paper reports the findings of a study conducted to find differences in self-perception with perception of others in order to identify a culturally sensitive method to explore social reality. The instruments measured how respondents rate themselves or others on several negative and positive descriptions of thoughts and behaviours. A sample of 100 respondents from diverse background in India rated predominantly positive and negative description of beliefs, values and preferences twice -- first for the people residing around them and then for themselves. They also rated themselves on a scale of social desirability. The findings confirmed that they attributed negative cognitions (beliefs, values and preferences) to the others more than themselves but attributed predominantly positive beliefs, values and preferences to themselves. The social desirability orientation was significantly related to respondents’ self but not to others’ perception. The findings thus suggested the use of informants rather than respondents in social research especially on sensitive issues such as ethical and moral behaviour.